2010
DOI: 10.1097/phm.0b013e3181c56287
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Postural Control During Trunk Bending and Reaching in Healthy Adults and Stroke Patients

Abstract: The difference of postural actions between groups depended on task demands. Small center of pressure displacement and fast center of pressure velocity characterized decreased adaptive postural actions. The amount of center of pressure shift and center of pressure velocity were also dependent on the task demands for both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
(63 reference statements)
4
24
0
Order By: Relevance
“…Asymmetric gait in chronic hemiplegia is characterized by longer time spent in affected single limb stance than unaffected single limb stance [33]. Recent studies on posturographic analysis observed that stroke patients tend to avoid shifting their center of pressure towards the hemiplegic side in sitting [34] and standing [35]. A study on involving the analysis of trunk kinematics during walking found that pelvic movements were unstable and asymmetrical in patients with stroke [36].…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric gait in chronic hemiplegia is characterized by longer time spent in affected single limb stance than unaffected single limb stance [33]. Recent studies on posturographic analysis observed that stroke patients tend to avoid shifting their center of pressure towards the hemiplegic side in sitting [34] and standing [35]. A study on involving the analysis of trunk kinematics during walking found that pelvic movements were unstable and asymmetrical in patients with stroke [36].…”
Section: Discussionmentioning
confidence: 99%
“…On measuring the center of pressure displacement during forward trunk bending and reaching in people after stroke, Chern et al . [3] observed less pressure distribution toward most affected side even the task demand was high. Posturography analysis revealed that balance ability after stroke as measured by Berg balance scale was strongly correlated to lateral weight shift ability than anterioposterior weight shifts.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Ability to transfer weight on paralyzed lower extremity is a prerequisite for functional mobility skills such as rising from a chair,[2] reach-outs in standing[3] and walking. [1] Perceptual dysfunction, sensory loss, poor motor recovery of lower extremity, spasticity, muscular weakness, poor trunk control, and altered pelvic alignment could contribute for reduced weight acceptance on the most affected lower limb.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that this particularly difficult movement in stroke is possibly caused by a combination of factors such as proximal hypertonia in the lower extremities or paresis of the trunk muscles and anteroposterior pelvic obliquity and rotation (Davis, 2003;Messier et al, 2004). However, the patients had some troubles when they shifted the center of gravity from sitting or standing to their paralyzed side (Van Nes et al, 2008;Chern et al, 2010). There may be a possibility exists that STE training may elevate symmetrical pelvic movement, thus better weight shifting towards hemiplegic limb during gait.…”
Section: ⅳ Discussionmentioning
confidence: 99%